Optimasi Vehicle Routing Problem With Time Windows (VRPTW) Pada Rute Mobile Grapari (MOGI) Telkomsel Cabang Malang Menggunakan Algoritme Genetika - Moch. Khabibul Karim; Budi Darma Setiawan; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sales Operation and Outlet (SOO) is one of Telkomsel's divisions. Sales Operation in transportation field is called Mobile Grapari (MOGI). Mogi operates every day, looking for sales points, but those points hasn't been effective in sales operation. The previous system was a manual scheduling by coordination between one MOGI with the other, causing occuring problem which is an empty point. This problem also leads to scheduling ineffectiveness at sales point which gives less than optimal results. One of causes is Vehicle Routing Problem with Time Windows (VRPTW). To overcome this problem, an optimization method called genetic algorithm is applied. Genetic algorithm is applied for solving point routes and sales profits. The test is performed to find the parameters that produce the best fitness value. The result of the test shows that the best population size is 450 with 2700 generation iteration and the combination of crossover and mutation rate are 0,2 and 0,9 respectively. Through this test, we get the best selection method that is elitism selection. The fitness value of best parameters is 0,5581. The effective route solution that is generated on Monday, First Car is in Arjosari (Terminal Area), Singosari (Samsat Singosari), and Karang Ploso Rest Area. Second Car is in Gadang (Terminal Hamidrusdi), Sudimoro (Pujas front SM Futsal Zone), and Kawi Atas Street. Third Car is located in Merjosari (Lap. Merjosari), Sigura-gura Street, (Home Aston Printer) and Tlogomas (Ruko Kopi Sosial) with Rp. 5.114.167.00 profit and Rp. 35.584.167,00 for a week.